Natural syntax: An introduction and application to special linguistic properties - OreÅ¡nik, Janez (Journal of Modern Languages, 2017)
Natural Syntax is a pseudo-deductive linguistic theory, and this is its most recent version. The naturalness judgements are couched in naturalness scales, which follow from the basic parameters (or “axioms”) listed at the beginning of this paper. The predictions of the theory are calculated in what are known as deductions, the chief components of each being a pair of naturalness scales and the rules governing the alignment of corresponding naturalness values. Parallel and chiastic alignment are distinguished and related to Henning Andersen’s early work on markedness. The basic idea is to illustrate how a (pseudo)deductive theory of syntax performs if it insists on avoiding abstract solutions, and in particular on excluding any generative component. Natural Syntax is exemplified here with (mostly individual) cases from the following languages: Chichewa, Gunin, Kambera, Northern Sotho, Saliba, Slovenian, Southern Tiwa, Wakiman, and Welsh.